Trends in research related to menopausal hormone therapy from 2000 to 2021: A bibliometric analysis - Li, Jing; Wei, Zhipeng; Wu, Jingxi; Min, Kaili; Li, Xiao; Yao, Yuan; Li, Yao; Zhang, Ningning; Shi, Anya; Han, Jiani; Qiao, Chengdong; Yang, Kehu (Frontiers in Medicine, 2022)
We conducted the present bibliometric analysis to explore menopausal hormone therapy (MHT)-related research trends between 2000 and 2021. The Web of Science database was systematically searched from 2000 to 2021 to retrieve MHT-related publications. Visualization mapping and keyword cluster graphs were utilized to illustrate the research topics and hotpots. We included 11,616 MHT-related publications for this bibliometric analysis. The results showed that (1) MHT-related research had a very slow increase in the past 22 years, and the trend fluctuated. Sum of times cited and average citations per item had the same trend: a sharp decline from 2002 to 2003, and a rapid increase from 2003 to 2006, reaching the peak in 2006, then following a downward trend. The average H-index was 57, peaking in 2001; (2) the USA, the League of European Research Universities, and Dr. JoAann Manson from Harvard University contributed the most; (3) Menopause: The Journal of The North American Menopause Society had the most significant number of MHT-related publications; (4) the research hotpots primarily focused on MHT for treating menopausal symptoms and the impact of MHT on women's health. According to previous studies, MHT was the most effective treatment for managing vasomotor symptoms of menopause, but results from the clinical trials and observational studies regarding MHT adverse events remain inconsistent. Mechanisms are fundamental when clinical studies give conflicting results. Therefore, future studies should focus on adverse events and their mechanisms.